A Rare Case of Suicide by Multiple Gunshot Wounds to the Head (Medico Legal Update, 2019)
Firearm injuries represent a significant topic of forensic pathology. The literature in this regard is innumerable, and can seem to have extensively covered the topic of this paper. However, the biological reality and the unpredictability of the concrete cases, continue and will always continue to present unusual circumstances that are worth examining for forensic pathologists. In this case report, we performed a comparative analysis between a particular case and the scientific literature. The case in question concerns suicide by single-shot short firearm, in which the subject shot himself three times on two sides of the head, without affecting the brain during its self-suppressive intent. Cases similar to this are always cause for reasonable doubt, which can only be solved with the contribution of forensic pathology and in-depth research.